Особливості проектування високочастотних синхронних генераторів для автономних енергетичних установок - Юр'єва, Олена Юріївна; Шайда, Віктор Петрович (НТУ "ХПІ", 2019)
Проаналізовано існуючі принципи обирання електромагнітних навантажень та головних розмірів синхронних машин. Виявлено принципи обирання головних розмірів та електромагнітних навантажень високочастотних генераторів у відповідності до номінальних даних, зазначених у технічному завданні. Сформульовано рекомендації щодо проектування високочастотних синхронних генераторів для автономних енергетичних установок. Отримано залежності, якими рекомендується користуватись при створенні нових високочастотних синхронних генераторів.

To provide recommendations on the principles of selecting the main sizes and electromagnetic loads of high-frequency synchronous generators for autonomous electric power installations. The proposed design principles are based on the use of a machine constant. Electro-magnetic loads are proposed to be determined through the apparent power of the generator. The relationship between the main dimensions and the nominal data is determined by analytical methods. The results of the design of synchronous generators according to the machine constant are analyzed. The discrepancy between the technical data of the designed synchronous generators and the calculated results was revealed. The proposed principles of developing a mathematical relationship between nominal data, electromagnetic characteristics and geometric sizes are based on the formula of the apparent power of the synchronous machine. The proposed approach to choosing the main dimensions does not contain any assumptions in the transformation of the EMF and the stator winding current to the magnetic induction in the air gap and the stator linear load, respectively. The dependences of the calculated volume of the machine on nominative apparent power at different rotation frequencies are determined in order to create the correct technical task for the design of a synchronous generator. Differences in determining the diameter of the rotor based on mechanical strength conditions were determined. Checking the correctness of determinated main dimensions and electromagnetic loads is the fulfillment of the requirements for the energy characteristics and the thermal state of the synchronous generator. Dependencies that are recommended for creating new high-frequency synchronous generators are found. These design features proposed for use in research and engineering practice.
Design features of high-frequency synchronous generators for autonomous power installations
Keywords: машинна постійна; головні розміри; електромагнітні навантаження; частота мережі; частота обертання; machine constant; main dimensions; electromagnetic loads; network frequency; rotation speed